Vapor–liquid critical properties of components of biodiesel. 2. Ethyl esters of n-alkanoic acids. (15th February 2016) - Nikitin, Eugene D.; Popov, Alexander P.
Highlights: Critical properties of five n -alkanoic acid ethyl esters were measured. These compounds are components of biodiesel. Equations for the estimation of the critical properties of esters were obtained. Abstract: The critical temperatures and the critical pressures of n -alkanoic acid ethyl esters C n H2 n − 1 O2 C2 H5 with n  = 10, 11, 12, 14, 16 have been measured by the pulse-heating technique. These esters are components of biodiesel. Equations for the calculation of the critical temperatures and pressures of ethyl esters of n -alkanoic acids have been obtained. Experimental critical properties have been compared with estimations made by these equations and by the group-contribution methods of Wilson and Jasperson, Constantinou and Gani, Cunico, Hukkerikar, Cerani, Sarupc, and Gani, and Nannoolal, Rarey, and Ramjugernath. The equations suggested in this study provide the best accuracy for the estimation of the critical properties of n -alkanoic acid ethyl esters with n from 5 to 16; these equations can be used for the calculation of the critical constants of heavier esters. The acentric factors of n -alkanoic acid ethyl esters have been estimated.